Clinical impact of the 0.2 µg/day fluocinolone acetonide intravitreal implant: outcomes from the ILUVIEN ® clinical evidence study in Portugal. - Carneiro, Angela; Meireles, Angelina; Castro Sousa, João Paulo; Teixeira, Carla (Therapeutic Advances in Ophthalmology, 2020)
Introduction: The ILUVIEN® (fluocinolone acetonide) Clinical Evidence in Portugal (ICE-PT) study is a retrospective, multicenter, observational study evaluating the effectiveness and safety of the FAc implant in patients with diabetic macular edema. Methods: Patients included in this study had received the 0.2 µg/day fluocinolone acetonide implant for the treatment of diabetic macular edema and had measurements of visual acuity and retinal thickness assessed by optical coherence tomography for at least 12 months pre- and post-fluocinolone acetonide implant administration, with ⩾2 follow-up visits. Outcomes measured included visual acuity, central foveal thickness, and intraocular pressure. Results: There was a significant increase in mean visual acuity compared with baseline at 3, 6, 9, and 12 months post-fluocinolone acetonide in both the overall study population and the pseudophakic subgroup (p < 0.05 at all time points in both groups). A significant reduction in mean central foveal thickness compared with baseline was seen in the overall study population at 3, 6, 9, and 12 months post-fluocinolone acetonide (p < 0.05 at all time points). At 12-month post-fluocinolone acetonide, a small but significant intraocular pressure increase of 1.0 mmHg was seen in the overall study population. Conclusion: The results of this analysis show that switching from the current standard of care to the fluocinolone acetonide implant leads to beneficial effects in terms of vision and retinal structure in patients with diabetic macular edema and that patients benefited from FAc implant administration, regardless of lens status.